The Bony Obliteration Tympanoplasty in Pediatric Cholesteatoma. Issue 9 (October 2015) - van Dinther, Joost J. S.; Vercruysse, Jean-Philippe; Camp, Sophie; De Foer, Bert; Casselman, Jan; Somers, Thomas; Zarowski, Andrzej; Cremers, Cor W. R. J.; Offeciers, Erwin
<x xml:space="preserve">Abstract</x> Objective: To present the safety and hygienic results of a 5-year longitudinal study in a pediatric population undergoing surgery for extensive cholesteatoma using a canal wall up approach with bony obliteration of the mastoid and epitympanic space. Study Design: Retrospective consecutive study. Patients: Thirty-three children (⩽18 yr) undergoing surgery for cholesteatoma (34 ears) between 1997 and 2009. Interventions: Therapeutic. Setting: Tertiary referral center. Main Outcome Measures: 1) Residual and recurrent cholesteatoma rates at 5-year postsurgery, 2) postoperative waterproofing and hygienic status of the ear, and 3) required operation rate to achieve the safety and hygienic goals. Results: At 5 years no patients were lost in follow-up. This consecutive series design is rare in chronical otitis media treatment reporting. The standard residual rate at 5 years was 5.8%, representing two residual cholesteatomas in the middle ear. The standard recurrence rate at 5 years was 2.9%, representing one recurrent cholesteatoma. At 5-year follow-up all ears were free of otorrhea and waterproof and all external ear canals were patent and self-cleaning. The operation rate to reach this safety and hygienic status was 1.5 operations per ear at 5-year follow-up. Conclusion: The use of a canal wall up approach with obliteration of the mastoid cavity and epitympanic space to surgically treat cholesteatoma in children results in low residual and recurrence rates and a high rate of trouble-free ears in the long term.